Manganese lithium ion porous adsorption membrane material and preparation method and application thereof
By using manganese-based lithium-ion porous adsorption film material during liquid lithium extraction, combining two-dimensional layered transition metal material and manganese lithium composite oxide, the problem of high dissolution rate of manganese element in the mixed matrix membrane is solved, and efficient lithium ion adsorption and selectivity are achieved.
Patent Information
- Application Number
- CN202411935408.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2044-12-26
AI Technical Summary
In the prior art, the dissolution rate of manganese elements in the mixed matrix membrane is high, resulting in the dissolution problem of metal elements during the liquid lithium extraction process.
Manganese-based lithium-ion porous adsorption film material is used. The preparation method includes combining the carbide, nitride or carbon nitride of the two-dimensional layered transition metal as a carrier, combining with the manganese lithium composite oxide and the film-forming polymer, forming a porous adsorption film through the phase conversion and effluent process to reduce the dissolution of manganese elements.
It effectively reduces the dissolution rate of manganese elements, improves the adsorption amount and selectivity of lithium ions, and solves the problem of high dissolution rate of metal elements in mixed matrix membranes.
Smart Images

Figure CN119857461A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of porous adsorption membrane materials, and in particular to manganese-based lithium ion porous adsorption membrane materials and preparation methods and applications thereof. Background Art
[0002] Lithium is widely used in industries such as energy and chemicals. Driven by the rapid growth of industries such as electric vehicles, the demand for lithium continues to increase. The main sources of lithium include lithium-containing ores and liquid lithium resources such as salt lake water, seawater, geothermal brine, and oil and gas production wastewater. Liquid lithium resources are currently the main source of lithium. Existing liquid lithium extraction technologies mainly include evaporation, precipitation, solvent extraction, electrochemical method, membrane separation and adsorption. Among these technologies, adsorption has become one of the main technologies for liquid lithium extraction due to its high selectivity, simple operation and high cost-effectiveness.
[0003] The existing liquid lithium extraction adsorbent materials mainly include titanium adsorbents and manganese adsorbents. The preparation process of titanium adsorbents is complicated and the preparation cost is high. The preparation method of manganese adsorbents is simple and has good adsorption effect, but manganese elements are easily dissolved during repeated use, causing adsorbent failure and water pollution.
[0004] Powdered lithium adsorbents are not conducive to recovery and regeneration in practical applications, and are prone to secondary pollution of water bodies. Therefore, powdered lithium adsorbents are usually formed into composite materials with various polymers, such as microspheres, fibers and mixed matrix membranes, etc., during use. Among them, mixed matrix membranes are a feasible solution for liquid lithium extraction, and do not require additional filtering steps during application, so secondary pollution can be effectively avoided. Although mixed matrix membranes can maintain the various properties of lithium adsorbents, metal elements still have a large dissolution rate after lithium adsorbents are prepared into mixed matrix membranes. Therefore, preventing the dissolution of metal elements in mixed matrix membranes during use is a technical problem to be solved in the field of liquid lithium extraction. Summary of the invention
[0005] The main purpose of the present invention is to provide a manganese-based lithium ion porous adsorption membrane material and a preparation method and application thereof, so as to solve the technical problem of high dissolution rate of manganese element in mixed matrix membrane in the prior art.
[0006] In order to achieve the above object, according to the first aspect of the present invention, a method for preparing a manganese-based lithium ion porous adsorption membrane material is provided, and the technical scheme is as follows:
[0007] The method for preparing a manganese-based lithium ion porous adsorption membrane material comprises the following steps:
[0008] The carrier is dispersed in an organic solvent, and then a film-forming polymer is added to form a uniform precursor solution; the carrier is a two-dimensional layered transition metal carbide, nitride or carbonitride;
[0009] Dispersing manganese-lithium composite oxide in a precursor solution to form a film casting solution;
[0010] The casting solution is coated on a support, and then phase-inverted by pure water to obtain a matrix membrane;
[0011] The matrix membrane is placed in a lithium eluting solution for immersion and washing to displace the lithium ions in the matrix membrane, thereby obtaining a manganese-based lithium ion porous adsorption membrane material.
[0012] As a further improvement of the preparation method of the above-mentioned manganese-based lithium ion porous adsorption membrane material: the preparation method of the carrier is:
[0013] The MAX phase material is selectively etched to obtain the MXene material;
[0014] The MXene material is modified to obtain a carrier.
[0015] As a further improvement of the preparation method of the above-mentioned manganese-based lithium ion porous adsorption membrane material:
[0016] The MAX phase material is Ti2AlC3, and the obtained MXene material is a two-dimensional layered Ti3C2; Ti2AlC3 is added to a mixture of lithium fluoride and hydrochloric acid for a water bath reaction, and after the reaction is completed, the precipitate is collected and washed to neutrality, and vacuum dried to obtain a two-dimensional layered Ti3C2;
[0017] The modification treatment comprises: immersing the MXene material in a modification solution, wherein the modification solution contains sodium hydroxide, ethylamine, acetamide and trimethylammonium chloride; collecting and drying the solid after the immersion is completed; and heat-treating the solid to obtain the carrier.
[0018] As a further improvement of the preparation method of the above-mentioned manganese-based lithium ion porous adsorption membrane material:
[0019] The mass ratio of lithium fluoride to hydrochloric acid is 1:(6.57-13.13); the mass ratio of Ti2AlC3 to lithium fluoride is 1:(1-3); the water bath temperature is 30-50°C, and the water bath time is 24-72 hours;
[0020] The mass fraction of the modified solution is 3% to 7%, and the molar ratio of sodium hydroxide, ethylamine, acetamide and trimethylammonium chloride is 1:1:1:1; the solid-liquid ratio of the impregnation is 1g:100mL, and after impregnation for 2 to 5 hours, the mixture is filtered, allowed to stand for 6 to 12 hours, dried, and then heat-treated in an inert gas at 600 to 800°C for 2 to 4 hours to obtain a carrier.
[0021] As a further improvement to the preparation method of the above-mentioned manganese-based lithium ion porous adsorption membrane material: the film-forming polymer is polysulfone; the organic solvent is at least one of 2-methylpyrrolidone, dimethylformamide, dimethylacetamide, and dimethyl sulfoxide; based on the total mass of the film-forming polymer and the organic solvent, the content of the film-forming polymer is 12 to 18 wt%; the mass ratio of the film-forming polymer to the carrier in the precursor solution is 1:(0.1 to 0.3).
[0022] As a further improvement of the preparation method of the above-mentioned manganese-based lithium ion porous adsorption membrane material: the preparation method of the manganese-lithium composite oxide is: calcining a mixed powder consisting of a lithium source and a manganese source in an air atmosphere, and obtaining the manganese-lithium composite oxide after cooling.
[0023] As a further improvement to the preparation method of the above-mentioned manganese-based lithium ion porous adsorption membrane material: the lithium source is selected from at least one of lithium carbonate, lithium hydroxide, and lithium nitrate; the manganese source is selected from at least one of manganese carbonate, manganese oxide, manganese dioxide, manganese trioxide, and manganese acetate; the molar ratio of lithium element to manganese element in the mixed powder is 1:(1.0-2.0); the calcination temperature is 350-750°C, and the calcination time is 2-12 hours.
[0024] As a further improvement to the method for preparing the above-mentioned manganese-based lithium ion porous adsorption membrane material: the mass ratio of the membrane-forming polymer to the manganese-lithium composite oxide in the casting solution is 1:(1-3).
[0025] In order to achieve the above object, according to the second aspect of the present invention, a manganese-based lithium ion porous adsorption membrane material is provided, and the technical solution is as follows:
[0026] The manganese-based lithium ion porous adsorption membrane material is prepared by the preparation method of the manganese-based lithium ion porous adsorption membrane material described in the first aspect; the average roughness value of the material is 31.5nm, the contact angle is 86.66°, and the FTIR spectrum is at 909cm -1 、650cm -1 、613cm -1 There are characteristic peaks.
[0027] In order to achieve the above object, according to the third aspect of the present invention, an application of a manganese-based lithium ion porous adsorption membrane material is provided, and the technical solution is as follows:
[0028] A lithium extraction method comprises placing the manganese-based lithium ion porous adsorption membrane material prepared by the preparation method described in the first aspect into a lithium-containing solution to adsorb lithium elements; or, using the manganese-based lithium ion porous adsorption membrane material prepared by the preparation method described in the first aspect to filter the lithium-containing solution.
[0029] The manganese-based lithium ion porous adsorption membrane material of the present invention and its preparation method and application have the following advantages: the present invention innovatively introduces a two-dimensional layered transition metal material, which not only increases the surface area and numerous adsorption sites and improves the adsorption capacity, but also can become a connecting bridge between the manganese-lithium composite oxide and the film-forming polymer through hydrogen bonds, and the increased hydrogen bonds can enhance the Mn-O bond energy, thereby hindering the dissolution of non-lithium metals. Compared with other metal ions, lithium ions show lower adsorption energy. Therefore, the dissolution of non-lithium metal elements can be effectively prevented while ensuring high adsorption capacity and high selectivity, effectively solving the technical problem of high dissolution rate of mixed matrix membranes in the prior art.
[0030] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments. Additional aspects and advantages of the present invention will be partially given in the following description, partially become apparent from the following description, or be learned through the practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] The drawings constituting a part of the present invention are used to assist the understanding of the present invention. The contents provided in the drawings and their related descriptions in the present invention can be used to explain the present invention, but do not constitute improper limitations on the present invention.
[0032] Figure 1 XRD patterns of LMO and HMO.
[0033] Figure 2 This is the SEM picture of LMO.
[0034] Figure 3 SEM photo of Ti3C2-MXene.
[0035] Figure 4 This is the SEM image of the cross section of PSF.
[0036] Figure 5 SEM image of the cross section of LMO / MXene / PSF.
[0037] Figure 6 SEM image of the cross section of HMO / MXene / PSF.
[0038] Figure 7 SEM image of the surface of HMO / MXene / PSF.
[0039] Figure 8 EDX element mapping image of the surface of HMO / MXene / PSF.
[0040] Fig. 9 Stress-strain curves of PSF and HMO / MXene / PSF.
[0041] Fig.10 FTIR spectra of PSF, HMO / PSF and HMO / MXene / PSF.
[0042] Fig.11 N2 adsorption-desorption isotherms and pore size distribution diagram of PSF.
[0043] Fig.12 N2 adsorption-desorption isotherms and pore size distribution diagram of HMO / MXene / PSF.
[0044] Fig.13 The cyclic stability diagram of HMO / MXene / PSF in LiCl aqueous solution.
[0045] Fig.14 Cyclic stability diagram of HMO / MXene / PSF in SGW.
[0046] Fig.15 Performance diagram of HMO / MXene / PSF in filtering LiCl aqueous solution.
[0047] Fig.16 Performance plot of SGW filtered for HMO / MXene / PSF. DETAILED DESCRIPTION
[0048] The present invention is described clearly and completely below in conjunction with the accompanying drawings. A person skilled in the art will be able to implement the present invention based on these descriptions. Before describing the present invention in conjunction with the accompanying drawings, it should be particularly noted that:
[0049] The technical solutions and technical features provided in each part of the present invention, including the following description, may be combined with each other if there is no conflict.
[0050] In addition, the embodiments of the present invention involved in the following description are generally only a part of the embodiments of the present invention, rather than all the embodiments. Therefore, based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0051] About the terms and units in the present invention: The terms "include", "have" and any variations thereof in the description and claims of the present invention and related parts are intended to cover non-exclusive inclusions.
[0052] The specific implementation of the manganese-based lithium ion porous adsorption membrane material and the preparation method thereof of the present invention is as follows:
[0053] (1) dispersing a carrier in an organic solvent, and then adding a film-forming polymer to form a uniform precursor solution; the carrier is a two-dimensional layered transition metal carbide, nitride or carbonitride;
[0054] (2) dispersing the manganese-lithium composite oxide in a precursor solution to form a film casting solution;
[0055] (3) coating the casting solution on a support, and then performing phase inversion with pure water to obtain a matrix membrane;
[0056] (4) The matrix membrane is placed in a lithium elution solution for immersion to displace the lithium ions in the matrix membrane, thereby obtaining a manganese-based lithium ion porous adsorption membrane material.
[0057] In step (1), the preparation method of the carrier is: selectively etching the MAX phase material to obtain a MXene material; modifying the MXene material to obtain the carrier;
[0058] The MXene is a two-dimensional layered Ti3C2, and the corresponding MAX phase material is Ti2AlC3. Ti2AlC3 is added to a mixture of lithium fluoride and hydrochloric acid for a water bath reaction. After the reaction is completed, the precipitate is collected and washed to neutrality, and vacuum dried to obtain a two-dimensional layered Ti3C2. Preferably, the mass ratio of lithium fluoride to hydrochloric acid is 1:(6.57-13.13); the mass ratio of lithium fluoride to Ti2AlC3 is 1:(1-3); the water bath temperature is 30-50°C, and the water bath time is 24-72 hours.
[0059] The modification treatment is as follows: immersing the MXene material in a modification solution containing sodium hydroxide, ethylamine, acetamide and trimethylammonium chloride; collecting and drying the solid after the immersion is completed; and heat-treating the solid to obtain a carrier. Preferably, the mass fraction of the modification solution is 3% to 7%, and the molar ratio of sodium hydroxide, ethylamine, acetamide and trimethylammonium chloride is 1:1:1:1; the solid-liquid ratio of the immersion is 1g:100mL, and the immersion is performed for 2 to 5 hours and then filtered, and then dried after standing for 6 to 12 hours, and then heat-treated in an inert gas at 600 to 800°C for 2 to 4 hours to obtain the carrier.
[0060] Preferably, the film-forming polymer is polysulfone; the organic solvent is at least one of 2-methylpyrrolidone, dimethylformamide, dimethylacetamide, and dimethyl sulfoxide; based on the total mass of the film-forming polymer and the organic solvent, the content of the film-forming polymer is 12 to 18 wt%.
[0061] Preferably, the mass ratio of the film-forming polymer to the carrier in the precursor solution is 1:(0.1-0.3).
[0062] In step (2), the preparation method of the manganese-lithium composite oxide is: calcining a mixed powder consisting of a lithium source and a manganese source in an air atmosphere, and obtaining a manganese-lithium composite oxide after cooling; preferably, the lithium source is selected from at least one of lithium carbonate, lithium hydroxide, and lithium nitrate; the manganese source is selected from at least one of manganese carbonate, manganese oxide, manganese dioxide, manganese trioxide, and manganese acetate; the molar ratio of lithium element to manganese element in the mixed powder is 1:(1.0~2.0); the calcination temperature is 350~750°C, and the calcination time is 2~12 hours.
[0063] Preferably, the mass ratio of the film-forming polymer to the manganese-lithium composite oxide in the casting solution is 1:(1-3).
[0064] In step (3), the support is a glass surface, a polypropylene non-woven fabric or a polyester resin non-woven fabric, and the thickness of the film casting knife is 200 μm.
[0065] In step (4), the lithium eluent is hydrochloric acid with a concentration of 0.5 to 1.5 mol / L, and the immersion time is 12 to 24 hours; after the hydrochloric acid immersion, the obtained manganese-based lithium ion porous adsorption membrane material is rinsed with ultrapure water and then stored in pure water.
[0066] The specific implementation of the lithium extraction method of the present invention is: the manganese-based lithium ion porous adsorption membrane material prepared by the above-mentioned preparation method is placed in a lithium-containing solution to adsorb lithium elements; or, the manganese-based lithium ion porous adsorption membrane material prepared by the above-mentioned preparation method is used to filter the lithium-containing solution.
[0067] The beneficial effects of the present invention are illustrated below by examples and test data.
[0068] Example 1: The steps for preparing the manganese-based lithium ion porous adsorption membrane material of this example are as follows:
[0069] 1 g of lithium fluoride was dissolved in 40 mL of hydrochloric acid solution to obtain a mixed solution (the mass ratio of lithium fluoride to hydrochloric acid was 1:13.13), 1 g of Ti2AlC3 was weighed and added to the mixed solution (the mass ratio of Ti2AlC3 to lithium fluoride was 1:1), and the mixture was reacted in a water bath at 30°C for 48 hours. After the reaction was completed, the mixture was repeatedly washed and centrifuged to neutrality, and vacuum dried at 60°C to obtain a two-dimensional layered Ti3C2, which was expressed as Ti3C2-MXene.
[0070] 1 g of Ti3C2-MXene was dispersed in 100 mL of a modified solution having a mass fraction of 5.2% and a molar ratio of sodium hydroxide, ethylamine, acetamide and trimethylammonium chloride of 1:1:1:1. After immersion for 3 hours, the solution was filtered, allowed to stand for 9 hours and then dried, and then heat treated in an inert gas at 700°C for 3 hours to obtain a carrier.
[0071] 0.16 g of the carrier was weighed and dispersed in 8.4 g of 2-methylpyrrolidone, and then 1.6 g of polysulfone was added to form a uniform precursor solution; the mass ratio of polysulfone to the carrier in the precursor solution was 1:0.1; based on the total mass of polysulfone and 2-methylpyrrolidone, the content of polysulfone was 16 wt%.
[0072] Lithium carbonate and manganese carbonate were mixed evenly to form a mixed powder (the molar ratio of lithium element to manganese element was 1:1.25), and then the mixed powder was calcined at 500° C. for 4 hours in an air atmosphere, and after cooling, a manganese-lithium composite oxide was obtained, which was expressed as LMO.
[0073] LMO is dispersed in the precursor solution to form a uniform casting solution; the mass ratio of polysulfone to LMO in the casting solution is 1:2.
[0074] The casting solution was coated on a polyester resin nonwoven fabric, and then a matrix membrane was obtained after phase inversion with pure water, which was expressed as LMO / MXene / PSF.
[0075] LMO / MXene / PSF was immersed in 1 mol / L hydrochloric acid for 24 hours to displace the lithium ions in the manganese-lithium composite oxide structure in LMO / MXene / PSF. After the hydrochloric acid immersion, it was rinsed with ultrapure water to obtain a manganese-based lithium ion porous adsorption membrane material, which was expressed as HMO / MXene / PSF.
[0076] After testing, the lithium adsorption capacity of HMO / MXene / PSF of this embodiment is 16.58 mg / g, and the manganese element dissolution rate is 1.35%.
[0077] Example 2: Compared with Example 1, the method for preparing the manganese-based lithium ion porous adsorption membrane material of this example is different in that the amount of the carrier is adjusted so that the mass ratio of polysulfone to the carrier in the precursor solution is 1:0.2.
[0078] After testing, the lithium adsorption capacity of HMO / MXene / PSF of this embodiment is 18.81 mg / g, and the manganese element dissolution rate is 0.45%.
[0079] Example 3: Compared with Example 1, the method for preparing the manganese-based lithium ion porous adsorption membrane material of this example is different in that the amount of the carrier is adjusted so that the mass ratio of polysulfone to the carrier in the precursor solution is 1:0.3.
[0080] After testing, the lithium adsorption capacity of HMO / MXene / PSF of this embodiment is 19.01 mg / g, and the manganese element dissolution rate is 0.13%.
[0081] Example 4: Compared with Example 2, the preparation method of the manganese-based lithium ion porous adsorption membrane material in this example is different in that the amount of LMO is adjusted so that the mass ratio of polysulfone to LMO in the casting solution is 1:2.5.
[0082] After testing, the lithium adsorption capacity of HMO / MXene / PSF of this embodiment is 19.99 mg / g, and the manganese element dissolution rate is 0.54%.
[0083] Example 5: Compared with Example 2, the preparation method of the manganese-based lithium ion porous adsorption membrane material in this example is different in that the amount of LMO is adjusted so that the mass ratio of polysulfone to LMO in the casting solution is 1:1.
[0084] After testing, the lithium adsorption capacity of HMO / MXene / PSF of this embodiment is 17.57 mg / g, and the manganese element dissolution rate is 0.24%.
[0085] Example 6: Compared with Example 2, the method for preparing the manganese-based lithium ion porous adsorption membrane material in this example is different in that the amount of LMO is adjusted so that the mass ratio of polysulfone to LMO in the casting solution is 1:1.5.
[0086] After testing, the lithium adsorption capacity of HMO / MXene / PSF of this embodiment is 15.65 mg / g, and the manganese element dissolution rate is 0.31%.
[0087] Example 7: Compared with Example 2, the preparation method of the manganese-based lithium ion porous adsorption membrane material in this example is different in that the amount of LMO is adjusted so that the mass ratio of polysulfone to LMO in the casting solution is 1:3.
[0088] After testing, the lithium adsorption capacity of HMO / MXene / PSF of this embodiment is 23.80 mg / g, and the manganese element dissolution rate is 0.83%.
[0089] Example 8: Compared with Example 4, the preparation method of the manganese-based lithium ion porous adsorption membrane material in this example is different in that the concentration of hydrochloric acid is adjusted so that the mass ratio of lithium fluoride to hydrochloric acid in the mixed solution is 1:6.57.
[0090] After testing, the lithium adsorption capacity of HMO / MXene / PSF of this embodiment is 19.43 mg / g, and the manganese element dissolution rate is 0.64%.
[0091] Example 9: Compared with Example 4, the preparation method of the manganese-based lithium ion porous adsorption membrane material in this example is different in that the concentration of hydrochloric acid is adjusted so that the mass ratio of lithium fluoride to hydrochloric acid in the mixed solution is 1:10.21.
[0092] After testing, the lithium adsorption capacity of HMO / MXene / PSF of this embodiment is 19.67 mg / g, and the manganese element dissolution rate is 0.61%.
[0093] Example 10: Compared with Example 9, the preparation method of the manganese-based lithium ion porous adsorption membrane material in this example is different in that the amount of manganese carbonate is adjusted so that the molar ratio of lithium element to manganese element in the mixed powder is 1:1.
[0094] After testing, the lithium adsorption capacity of HMO / MXene / PSF of this embodiment is 17.54 mg / g, and the manganese element dissolution rate is 0.35%.
[0095] Example 11: Compared with Example 9, the preparation method of the manganese-based lithium ion porous adsorption membrane material in this example is different in that the amount of manganese carbonate is adjusted so that the molar ratio of lithium element to manganese element in the mixed powder is 1:2.
[0096] After testing, the lithium adsorption capacity of HMO / MXene / PSF of this embodiment is 18.23 mg / g, and the manganese element dissolution rate is 0.83%.
[0097] Example 12: Compared with Example 9, the method for preparing the manganese-based lithium ion porous adsorption membrane material in this example is different in that the amount of Ti2AlC3 is adjusted so that the mass ratio of Ti2AlC3 to lithium fluoride is 1:2.
[0098] After testing, the lithium adsorption capacity of HMO / MXene / PSF of this embodiment is 18.98 mg / g, and the manganese element dissolution rate is 0.72%.
[0099] Example 13: Compared with Example 9, the method for preparing the manganese-based lithium ion porous adsorption membrane material in this example is different in that the amount of Ti2AlC3 is adjusted so that the mass ratio of Ti2AlC3 to lithium fluoride is 1:3.
[0100] After testing, the lithium adsorption capacity of HMO / MXene / PSF of this embodiment is 19.12 mg / g, and the manganese element dissolution rate is 0.71%.
[0101] Among the above embodiments, embodiment 7 is the most preferred embodiment. Based on embodiment 7, a control experiment was conducted to fully illustrate the lithium adsorption mechanism of the HMO / MXene / PSF of the present invention.
[0102] Comparative Example 1: LMO was directly treated with hydrochloric acid to obtain a powdery manganese-based lithium ion adsorption material, denoted as HMO.
[0103] Comparative Example 2: Polysulfone alone was used to form a membrane, and the obtained membrane was denoted as PSF.
[0104] Comparative Example 3: LMO was directly dispersed in polysulfone and an organic solvent without using a carrier. The membrane before elution was denoted as LMO / PSF, and the membrane formed after elution was denoted as HMO / PSF.
[0105] The test results show that the manganese dissolution rates of HMO, HMO / PSF, and HMO / MXene / PSF are 14.17%, 8.58%, and 0.42%, respectively, indicating the effectiveness of strong hydrogen bonds in reducing manganese loss.
[0106] Comparative Example 4: Ti3C2-MXene is directly used, that is, Ti3C2-MXene and polysulfone are dispersed in 2-methylpyrrolidone to form a uniform precursor solution. The test results show that the lithium adsorption capacity of the membrane material of this comparative example is 18.65 mg / g, which is significantly reduced compared with Example 7, indicating that the functional groups (hydroxyl-OH, amine-NH2, quaternary ammonium salt-N+(CH3)3, amide-CONH2) introduced by the modification treatment can significantly improve the lithium adsorption effect.
[0107] The average roughness (Ra) value of PSF is 6.75nm, and the Ra value of HMO / MXene / PSF is 31.5nm. It can be seen that the addition of nanoparticles significantly changes the membrane surface texture, thereby affecting the surface morphology and permeability. The membrane with a rough surface exhibits an enhanced surface area, thereby enhancing the water flux and adsorption capacity of the membrane.
[0108] The contact angle of PSF was tested to be 81.39°, while that of HMO / MXene / PSF was 86.66°. It can be seen that the increase in surface roughness increases the contact area between the solid phase and the liquid phase, thereby increasing the apparent geometric surface area and enhancing the surface hydrophobicity.
[0109] Figure 1 is the XRD pattern of LMO and HMO. Figure 1 As shown, the XRD pattern of LMO is similar to that of the original cubic spinel Li 1.33 Mn 1.67 O4 (card number PDF018-0026). The spinel peak of the XRD spectrum of HMO shifts slightly to a higher 2θ value. This shift is attributed to the Li + / H + Exchange reaction.
[0110] Figure 2 This is the SEM photo of LMO. Figure 2 As shown, LMO exhibits a nanosheet-like morphology.
[0111] Figure 3 This is the SEM picture of Ti3C2-MXene. Figure 3As shown, Ti3C2-MXene has a layered structure composed of closely stacked nanosheets.
[0112] Figure 4 This is the SEM image of the cross section of PSF. Figure 5 SEM image of the cross section of LMO / MXene / PSF. Figure 6 SEM image of the cross section of HMO / MXene / PSF. Figure 7 SEM image of the surface of HMO / MXene / PSF. Figure 8 This is the EDX element mapping image of the surface of HMO / MXene / PSF. Figure 4-5 As shown in Figure 2, after loading Ti3C2-MXene and LMO, the membrane porosity of LMO / MXene / PSF increased significantly compared to that of PSF. Figure 6-7 As shown in Figure 2, the surface porosity of HMO / MXene / PSF increased significantly compared with that of LMO / MXene / PSF, indicating that the excess load was removed during the leaching process. Figure 8 As shown, C, O, Mn, F, Cl, Ti, and S are uniformly distributed in HMO / MXene / PSF.
[0113] X-ray photoelectron spectroscopy (XPS) analysis revealed that the percentages of C, O, Mn and Ti were 50.34 wt%, 23.84 wt%, 24.31 wt% and 0.5 wt%, respectively.
[0114] Fig. 9 is the stress-strain curve of PSF and HMO / MXene / PSF. Fig. 9 As shown, HMO / MXene / PSF exhibits a maximum tensile stress of 1.75 MPa and a strain of 112.10%, both of which are slightly lower than those of PSF.
[0115] Fig.10 FTIR spectra of PSF, HMO / PSF and HMO / MXene / PSF. Fig.10 As shown in Figure 2, compared with PSF and HMO / PSF, HMO / MXene / PSF has a -1 、650cm -1 、613cm -1 The vibration peak at indicates that the adsorption process of lithium is the exchange of hydrogen in HMO with lithium.
[0116] Fig.11 N2 adsorption-desorption isotherms and pore size distribution diagram of PSF. Fig.12 N2 adsorption-desorption isotherms and pore size distribution diagram of HMO / MXene / PSF. Figure 11-12As shown in Figure 2, the N2 adsorption-desorption isotherms all conform to the typical IV type isotherm with H3 type hysteresis loops, indicating the presence of mesopores. The surface area of PSF is 18.55 m 2 / g, while HMO / MXene / PSF exhibits a significantly increased surface area of 36.98 m 2 The pore size distribution diagram also shows that after loading LMO and Ti3C2-MXene, the membrane pore size has changed significantly. The average pore size of PSF is 25.63nm, while the average pore size of HMO / MXene / PSF is 11.83nm.
[0117] In the adsorption performance test, the lithium adsorption amount was tested by adding the membrane material to a glass bottle containing a LiCl aqueous solution (pH = 12) and shaking it on a rotary shaker at a speed of 200 rpm for 72 hours. The lithium adsorption amount (q e ) is calculated using the following formula:
[0118]
[0119] Dominant partition coefficient (K d ) is calculated using the following formula:
[0120]
[0121] Among them, q e (mg / g) is the amount of lithium adsorption, indicating the adsorption capacity at equilibrium; V(L) is the volume of LiCl aqueous solution; m(g) is the mass of HMO / MXene / PSF, C0 and C e Represent the initial concentration and equilibrium concentration of lithium ions in LiCl aqueous solution (mg / L), respectively.
[0122] The manganese dissolution rate is the percentage of the manganese mass in the solution after the adsorption reaction is completed to the manganese mass in HMO / MXene / PSF, wherein the manganese mass in HMO / MXene / PSF is calculated based on the amount of manganese source used, and the manganese mass in the solution after the adsorption reaction is completed is calculated after the manganese concentration is detected by inductively coupled plasma optical emission spectroscopy (ICP-OES) test.
[0123] Shale gas wastewater (SGW) was used for lithium adsorption and filtration. The initial concentration of the main metal ions in SGW was: 25.6 mg / L Li + 、7810mg / LNa + , 251mg / LK + 、239mg / L Ca 2+ 、364.5mg / L Ba 2+The adsorption effect of HMO / MXene / PSF on SGW is shown in Table 1.
[0124] Table 1
[0125] Metal ions Initial concentration (mg / L) Equilibrium concentration (mg / L) Adsorption capacity (mg / g) <![CDATA[K d (mL / g)]]> <![CDATA[Li + ]]> 25.6 15.01 21.18 1411.06 <![CDATA[Na + ]]> 7810 7802 16 2.05 <![CDATA[K + ]]> 251 245.3 11.4 46.47 <![CDATA[Ca 2+ ]]> 239 236.52 4.96 20.97 <![CDATA[Ba 2+ ]]> 364.5 363 3 8.26
[0126] As shown in Table 1, the lithium adsorption of HMO / MXene / PSF on SGW is 21.18 mg / g, the sodium adsorption is 16 mg / g, the potassium adsorption is 11.4 mg / g, the calcium adsorption is 4.96 mg / g, and the barium adsorption is 3 mg / g. The K of HMO / MXene / PSF for lithium ions is calculated to be d It is 1411.06mL / g, which is significantly higher than other ions, indicating that it has a higher affinity for lithium ion adsorption and better selectivity.
[0127] The adsorbed lithium ions were removed by acid washing, followed by subsequent adsorption cycles to evaluate the regeneration performance of HMO / MXene / PSF. Fig.13 The cyclic stability diagram of HMO / MXene / PSF in LiCl aqueous solution. Fig.14 The cyclic stability diagram of HMO / MXene / PSF in SGW. Figure 13-14 As shown, in LiCl aqueous solution and SGW, the lithium adsorption capacity after each regeneration remains relatively stable, with excellent usage stability.
[0128] The flux of PSF and HMO / MXene / PSF was evaluated using a Merck Millipore stirred tank apparatus (8050, USA) with a filtration module diameter of 4 cm and filtration at a transmembrane pressure (TMP) of 0.04 MPa. The flux was calculated using the following formula:
[0129]
[0130] In the formula, J(L / m 2 h) is the flux; Q(L) is the volume of filtrate obtained, Δt(h) is the time interval, A(m 2 ) is the operating surface area of the membrane material, which is 12.56 cm 2 .
[0131] When the filtered liquid is pure water, the pure water flux of PSF is only 10L / m 2 / h, while the pure water flux of HMO / MXene / PSF is 120L / m 2 / h.
[0132] Fig.15 Performance diagram of HMO / MXene / PSF in filtering LiCl aqueous solution. Fig.16Performance graph of SGW filtered for HMO / MXene / PSF. Figure 15-16 As shown in the figure, when the filtered liquid is a LiCl aqueous solution (C0 is 20.5 mg / L), the lithium ion concentration reaches a maximum value when the filtrate volume is 200 mL. When the filtered liquid is SGW (C0 is 25.6 mg / L), the lithium ion concentration reaches a maximum value when the filtrate volume is 160 mL. It can be seen that the HMO / MXene / PSF of the present invention can adsorb lithium while filtering.
[0133] The equipment used for the above tests and characterizations is:
[0134] The roughness was analyzed by atomic force microscopy (AFM) using a Bruker Multimode 8.
[0135] Contact Angle (CA) Use Contact angle measurement.
[0136] The XRD spectrum was obtained using an X-ray diffraction analyzer from SHIMADZU, Japan, using a CuKα radiation target (40 kV, 30 mA).
[0137] The SEM images and EDX element mapping images were obtained using a scanning electron microscope (SEM) from ZEISS, Germany.
[0138] The stress-strain curves were analyzed using a UTM5305H tensile tester.
[0139] X-ray photoelectron spectroscopy (XPS) measurements were collected using a Thermo ESCALAB 250XI.
[0140] Fourier transform infrared (FT-IR) spectra were collected using an Agilent 1260.
[0141] The specific surface area was determined by QUADRASORB SI and the pore structure was determined using Brunauer-Emmett-Teller (BET).
[0142] Inductively coupled plasma optical emission spectroscopy (ICP-OES) was used to determine the concentration of lithium ions and other ions, specifically an Optima 8000 model.
[0143] The above is a description of the relevant contents of the present invention. A person skilled in the art will be able to implement the present invention based on these descriptions. Based on the above contents of the present invention, all other embodiments obtained by a person skilled in the art without creative work shall fall within the scope of protection of the present invention.
Claims
1. A method for preparing a manganese-based lithium ion porous adsorption membrane material, characterized in that: The following steps are involved: The carrier is dispersed in an organic solvent, and then a film-forming polymer is added to form a uniform precursor solution; the carrier is a two-dimensional layered transition metal carbide, nitride or carbonitride; Dispersing manganese-lithium composite oxide in a precursor solution to form a film casting solution; The casting solution is coated on a support, and then phase-converted by pure water to obtain a matrix membrane; The matrix membrane is placed in a lithium eluting solution for immersion and washing to displace the lithium ions in the matrix membrane, thereby obtaining a manganese-based lithium ion porous adsorption membrane material.
2. The method for preparing a manganese-based lithium ion porous adsorption membrane material according to claim 1, characterized in that: The preparation method of the carrier is: The MAX phase material is selectively etched to obtain the MXene material; The MXene material is modified to obtain a carrier.
3. The method for preparing a manganese-based lithium ion porous adsorption membrane material according to claim 2, characterized in that: The MAX phase material is Ti2AlC3, and the obtained MXene material is a two-dimensional layered Ti3C2; Ti2AlC3 is added to a mixture of lithium fluoride and hydrochloric acid for a water bath reaction, and after the reaction is completed, the precipitate is collected and washed to neutrality, and vacuum dried to obtain a two-dimensional layered Ti3C2; The modification treatment comprises: immersing the MXene material in a modification solution, wherein the modification solution contains sodium hydroxide, ethylamine, acetamide and trimethylammonium chloride; collecting and drying the solid after the immersion is completed; and heat-treating the solid to obtain the carrier.
4. The method for preparing a manganese-based lithium ion porous adsorption membrane material according to claim 3, characterized in that: The mass ratio of lithium fluoride to hydrochloric acid is 1:(6.57-13.13); the mass ratio of Ti2AlC3 to lithium fluoride is 1:(1-3); the water bath temperature is 30-50°C, and the water bath time is 24-72 hours; The mass fraction of the modified solution is 3% to 7%, and the molar ratio of sodium hydroxide, ethylamine, acetamide and trimethylammonium chloride is 1:1:1:1; the solid-liquid ratio of the impregnation is 1g:100mL, and after impregnation for 2 to 5 hours, the mixture is filtered, allowed to stand for 6 to 12 hours, dried, and then heat-treated in an inert gas at 600 to 800°C for 2 to 4 hours to obtain a carrier.
5. The method for preparing a manganese-based lithium ion porous adsorption membrane material according to claim 3, characterized in that: The film-forming polymer is polysulfone; the organic solvent is at least one of 2-methylpyrrolidone, dimethylformamide, dimethylacetamide, and dimethyl sulfoxide; based on the total mass of the film-forming polymer and the organic solvent, the content of the film-forming polymer is 12 to 18 wt %; the mass ratio of the film-forming polymer to the carrier in the precursor solution is 1:(0.1 to 0.3).
6. The method for preparing a manganese-based lithium ion porous adsorption membrane material according to claim 1, characterized in that: The preparation method of the manganese-lithium composite oxide is as follows: calcining a mixed powder consisting of a lithium source and a manganese source in an air atmosphere, and obtaining the manganese-lithium composite oxide after cooling.
7. The method for preparing a manganese-based lithium ion porous adsorption membrane material according to claim 6, characterized in that: The lithium source is selected from at least one of lithium carbonate, lithium hydroxide, and lithium nitrate; the manganese source is selected from at least one of manganese carbonate, manganese oxide, manganese dioxide, manganese trioxide, and manganese acetate; the molar ratio of lithium element to manganese element in the mixed powder is 1:(1.0-2.0); the calcination temperature is 350-750°C, and the calcination time is 2-12 hours.
8. The method for preparing a manganese-based lithium ion porous adsorption membrane material according to claim 1, characterized in that: The mass ratio of the film-forming polymer to the manganese-lithium composite oxide in the casting solution is 1:(1-3).
9. A manganese-based lithium ion porous adsorption membrane material, characterized in that: The material is prepared by the method for preparing a manganese-based lithium ion porous adsorption membrane material according to any one of claims 1 to 8; the average roughness value of the material is 31.5nm, the contact angle is 86.66°, and the FTIR spectrum is at 909cm -1 、650cm -1 、613cm -1 There are characteristic peaks.
10. A lithium extraction method, characterized in that: The manganese-based lithium ion porous adsorption membrane material prepared by the preparation method described in any one of claims 1-7 is placed in a lithium-containing solution to adsorb lithium elements; or, the manganese-based lithium ion porous adsorption membrane material prepared by the preparation method described in any one of claims 1-7 is used to filter the lithium-containing solution.
Citation Information
Patent Citations
Two-dimensional composite confinement MnO2.2. 3H2O coated MC membrane, preparation method thereof and application of membrane in extraction of lithium from seawater
CN116251482A
Method for preparing lithium ion selective two-dimensional layered membrane by using lithium adsorbent
CN118179279A
Two-dimensional carbon material modified lithium ion sieve composite membrane and preparation method thereof
CN118892809A
Cited By
Titanium lithium adsorbent and preparation method thereof
CN120346779A